Introduzione - Amato, Salvatore (Teoria e Critica della Regolazione Sociale / Theory and Criticism of Social Regulation, 2020)
Converging technologies are moving in so many and different directions, that it becomes fundamentally necessary to rethink certain legal categories. How many autonomous software agents do transform the way we live and work? Law will be challenged to learn how to manage new technological capabilities and protect the fundamental human rights. Keywords: Life 3.0; Industry 4.0; Homo tecnicus; Digital properties; Neuroscience.